Pengaruh Teknologi Hotel (Smart Hospitality) Terhadap Loyalitas Tamu Dengan Mediasi Kepuasan Tamu Hotel - Fran Serano Andres; Aznil Mardin (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2025)
This study aims to analyze the effect of hotel technology (smart hospitality) on guest loyalty, mediated by guest satisfaction. The adoption of technology in the hospitality industry has become a key factor in enhancing competitiveness and guest experience. This study employs a quantitative approach with an explanatory design using Structural Equation Modeling (SEM) based on PLS, involving 195 respondents who are guests of star-rated hotels in West Sumatra. The variables measured include Smart Hospitality Technology (Perceived Ease of Use and Perceived Usefulness), Guest Satisfaction, and Guest Loyalty. The results indicate that Perceived Ease of Use (β=0.242, p<0.001) and Perceived Usefulness (β=0.192, p<0.001) have a significant positive effect on guest satisfaction. Guest satisfaction has a significant positive effect on guest loyalty (β=0.563, p<0.001). The mediation test shows that guest satisfaction mediates the relationship between Perceived Ease of Use (β=0.136, p<0.001) and Perceived Usefulness (β=0.108, p<0.001) on guest loyalty. These results confirm that the implementation of hotel technology that is easy to use and beneficial can increase guest satisfaction, which in turn contributes to guest loyalty. These findings have practical implications for hotel management in developing digitalization strategies focused on the guest experience.